Coaxial nanofibrous scaffolds mimicking the extracellular matrix transition in the wound healing process promoting skin regeneration through enhancing immunomodulation. Issue 5 (19th January 2021) - Sun, Luyao; Li, Jing; Gao, Wendong; Shi, Miao; Tang, Fengling; Fu, Xiaoling; Chen, Xiaofeng
Abstract : A degradable coaxial nanofibrous scaffold that mimics ECM transition in the wound healing process is designed to achieve better healing outcomes. Abstract : Numerous studies have shown that scaffolds incorporated with extracellular matrix (ECM) proteins could regulate cell behaviors and improve wound healing. However, most ECM-containing scaffolds fail to capture the dynamic features of the native ECM. In this regard, nanofibrous scaffolds which mimic the composition transition of the ECM during wound healing may have great potential in promoting skin regeneration through dynamically modulating the microenvironment. Herein, we report a novel skin ECM-biomimetic coaxial nanofibrous scaffold for the repair of chronic wounds. Two essential ECM proteins, fibrinogen and collagen I, were incorporated into the shell and the core of nanofibers, respectively, to mimic the sequential appearance of fibrinogen and collagen I in the wound healing process. The regulation of the biomimetic coaxial scaffolds on adipose-derived mesenchymal stromal cells (ASCs) was compared with that of the PLGA/fibrinogen, PLGA/collagen I and PLGA uniaxial scaffolds. Our results showed that the biomimetic coaxial scaffolds remarkably promoted the immunomodulatory paracrine secretion of ASCs. By incubating macrophages with ASC conditioned medium, the enhanced immunomodulation of ASCs on the biomimetic coaxial scaffolds was confirmed by the enhanced M1-to-M2 polarization of macrophages. Furthermore, the biomimetic coaxial scaffolds effectively promoted wound repair through resolving inflammation in diabetic rats. These findings helped reveal the role of the dynamic ECM change in regulating wound healing and suggest the potential utility of the biomimetic coaxial scaffolds as a promising alternative to treat chronic wounds.